PRAKTEK CORPORATE SOCIAL RESPONSIBILITY (CSR) DI PERUSAHAAN MULTINASIONAL - Titisari, Kartika Hendra (Universitas Muhammadiyah Surakarta, 2017)
Purpose - In line with the stakeholder, social contract, and the legitimacy theory of the companys obligations under the CSR to maintain sustainability. The purpose of this article is to know the CSR practices of multinational companies in various countries.Design / methodology / approach - Overview is based on 15 articles published from 2007 to 2015 in academic databases are Emerald and Proquest with keywords CSR, MNC, and Multinational.Findings - Through a review of the literature, this paper presents the implementation of CSR in multinational companies in various countries, which requires the active participation of stakeholders.Study limitations / implications - The literature on the implementation of CSR is little available.Originality - This paper presents a review of literature on an important aspect in the implementation of CSR strategies of multinational companies, namely the social maturity of the international community and cultural evolution of political thought, social adaptation activities of multinational companies, and market diversification.Keywords: CSR, MNC, MultinationalType of paper: Literature Review